The Care Dependency Scale: A cross validation study in inpatients with cancer. (February 2022) - Piredda, Michela; Candela, Maria Luigia; Marchetti, Anna; Biagioli, Valentina; De Maria, Maddalena; Facchinetti, Gabriella; Albanesi, Beatrice; Iacorossi, Laura; De Marinis, Maria Grazia
Abstract: Purpose: Inpatients with cancer are likely to experience care dependency and would benefit from nurses' evaluation of such dependency. The Care Dependency Scale (CDS) is a 15-item instrument widely used to assess patients' dependency in different populations and settings. This study aimed to test the psychometric properties of the proxy Italian version of the CDS in inpatients with cancer. Methods: A multicentre cross-sectional cross-validation study was conducted between February 2016 and October 2017 in a convenience sample of 517 adult patients with cancer admitted to four hospitals in Italy. The sample was randomly divided into two subsamples. The factor structure of the CDS based on previous studies was tested on a subsample through confirmatory factor analyses (CFAs). The best fitting model was cross-validated through CFA on the second subsample and on the total sample. Results: The sample mean age was 65.68 years, 51.5% were male. The CFAs performed on the first subsample (n = 258), on the second subsample (n = 259) and on the total sample yielded acceptable fit indexes. The factors Physical care dependency and Psychosocial care dependency with a second-order factor were confirmed. Reliability in terms of internal consistency and inter-rater reliability were satisfactory. Conclusions: The Care Dependency Scale is a tool able to assess the level of care dependency in patients with cancer with adequate validity and reliability. The Care Dependency Scale can help to distinguish between physical and psychosocial needs and to create a base for personalized patient care. Highlights: What is already known about the topic? The Care Dependency Scale (CDS) is a specific measure of nursing care dependence. Oncology nurses need an instrument to measure the patients' degree of care dependency. What this paper adds The CDS is valid and reliable and can be used by oncology nurses helping them to distinguish physical and psychosocial care dependence. The CDS helps nurses to identify the patient' needs and plan individualized care.